Influence Of Caffeine On The Redox Characteristics Of Iron In Aqueous Solution - Jabbar, Md. Abdul; Kabir, Md. Humayun; Chowdhury, Reaz Ahmed (Journal of the Bangladesh Chemical Society, 2013)
Electrochemical investigation of the influence of caffeine on the redox behaviour of iron (Fe) was studied by using cyclic voltammetry (CV) and chronocoulometry (CC) in aqueous solution. It was found that caffeine retards the heterogeneous charge transfer of Fe due to the formation of Fe-caffeine complex. Qualitative information for the formation of Fe-caffeine complex was obtained from CV and CC data. Jobs plot suggested that a 1:1 complex of Fe-caffeine was formed in aqueous media. The active center of caffeine for the formation of Fe-caffeine complex was found between O(33) and O(34) position, revealed from MOPAC (Semi-empirical computation, molecular orbital packagePM3) computation. Journal of Bangladesh Chemical Society, Vol. 25(2), 166-179, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15083